2022
DOI: 10.1021/acs.biomac.1c01532
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Antimicrobial Peptides Based on Constitutional Isomerism-Dictated Self-Assembly

Abstract: Self-assembly has been identified as an innovative strategy for improving the antimicrobial efficacy and bioavailability of short peptides. However, the detailed molecular information of short peptides linking to the self-assembly structures and antimicrobial activity remains to be more clearly understood. This work reported that the constitutional isomeric sequences of cationic peptides showed a significant impact on their antimicrobial activity. We investigated the self-assembly structures of two constitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…We also propose that our active learning screening approach can be generically extended to other applications in biopolymer and biomolecular design where it is necessary to navigate large sequence spaces by coupling the GPR/BO approach to alternative computational and/or experimental measures of performance such as protein-ligand binding free energy 88 or antimicrobial activity. 89,90 Author contributions Table 1 Top 10 candidates identified by active learning computational screen along with their computed ΔG value, round of discovery in the active learning screen, and hydropathy score of the X 1 and X 2 guest residues under the Kyte-Doolittle hydropathy scale. 23 The abbreviation (X 1 ) m (X 2 ) n stands for (…”
Section: Msde Paper 4 Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also propose that our active learning screening approach can be generically extended to other applications in biopolymer and biomolecular design where it is necessary to navigate large sequence spaces by coupling the GPR/BO approach to alternative computational and/or experimental measures of performance such as protein-ligand binding free energy 88 or antimicrobial activity. 89,90 Author contributions Table 1 Top 10 candidates identified by active learning computational screen along with their computed ΔG value, round of discovery in the active learning screen, and hydropathy score of the X 1 and X 2 guest residues under the Kyte-Doolittle hydropathy scale. 23 The abbreviation (X 1 ) m (X 2 ) n stands for (…”
Section: Msde Paper 4 Discussion and Conclusionmentioning
confidence: 99%
“…We also propose that our active learning screening approach can be generically extended to other applications in biopolymer and biomolecular design where it is necessary to navigate large sequence spaces by coupling the GPR/BO approach to alternative computational and/or experimental measures of performance such as protein–ligand binding free energy 88 or antimicrobial activity. 89,90…”
Section: Discussionmentioning
confidence: 99%
“…S4 (ESI †), Pep1 by itself showed two bands at 1632 and 1675 cm À1 ; the band at 1632 cm À1 was assigned to the dominant random coil together with other conformations during the freeze-drying step. 39 The turn and b-sheet conformation are most likely to exist, but have very low populations. 40 The band at 1675 cm À1 was ascribed to the formation of trifluoroacetate salts during the synthesis purification process of Pep1.…”
Section: Molecular Conformations Of Pep1 and Pep1-po 4 3àmentioning
confidence: 99%
“…In addition, the distinct selfassembly structures of a pair of oligopeptide sequence isomers dictated the antimicrobial activity. 16 Dendrimers, or dendritic molecules with a regular branching architecture, are one of the common self-assembling macromolecules. Pioneered by Percec and co-workers, the systematic study of a series of so-called Percec-type dendrons revealed diverse-ordered nanostructures, mainly correlated to a parameter known as the molecular solid angle.…”
mentioning
confidence: 99%
“…However, given the recent progress, such as the iterative exponential growth strategy, the extreme difficulties and low efficiency in synthesizing uniform, sequence-controlled macromolecules still limit the study in this direction, with a handful of examples focusing on linear macromolecules. , Changes in monomer sequence of linear block copolymers may alter the overall molecular shape, thus inducing the phase evolution from lamellae to cylinders and spheres. In addition, the distinct self-assembly structures of a pair of oligopeptide sequence isomers dictated the antimicrobial activity …”
mentioning
confidence: 99%